Is it really better to "die" than "live"? Reflections on the practice of "death with dignity" in China - Long Chen; Minghui Ren (Frontiers Media S.A., 2024)
AimTo analyze the causes of the controversy caused by "death with dignity" in China, and to provide some useful thoughts for the practical exploration of "death with dignity."Subject and methodsBy combing the periodical literature, legal texts and practice, we find that the Medical Regulations of Shenzhen Special Economic Zone, which was revised and passed by China in 2022, recognized the legal effect of "living will" for the first time in legislation, which triggered a wide-ranging social discussion on "death with dignity" and brought many controversies.ResultsDue to the influence of traditional culture, policies and laws, medical service supply capacity and other factors, death with dignity suffers from great practical resistance.ConclusionThe exploration of "death with dignity" system needs to start with the problems encountered in practice, focusing on cultivating a good system implementation environment, strengthening the top-level design of "death with dignity" system, and improving the national social security system for hospice care.